Efektifitas Penyuluhan tentang Sayuran Menggunakan Media “Kartu Sayuran” terhadap Peningkatan Pengetahuan Siswa Sekolah Dasar - Dina Fadhilah; Th Ninuk Sri Hartini; I Made Alit Gunawan (Poltekkes Kemenkes Yogyakarta, 2017)
Background: Vegetable consumption of Indonesian population, especially children still not in accordance with government recommendations are 4-5 servings a day. Elementary school student is a very decisive period of good growth and development. A balanced nutritious food intake is essential to ensure healthy and active child growth. If eating habits by applying healthy and balanced nutritious food early given, then the habit will affect until growing up later. Nutrition education efforts in schools have a great opportunity to successfully improve the knowledge about nutrition among the community because the school students are expected to be a bridge for teachers with their parents, teachers as educators in teaching and learning process have an influence on their students. The right media will increase enthusiasm self-study according to the environment and enable students to learn by themselves according to their interests and abilities. Objective: This research are Quasi experiment (experiment) is doing experimental activities, which aims to determine the effects that arise, as a result of a particular treatment Method:. Research design is “pre test and post test with contol group design”. The subjects of the study were 30 student of elementary school from SDN Godean 1 as a counseling group and 30 students from SDN Godean 2 as a group of vegetable cards. Result: The results concluded that there was no difference in the level of knowledge of the sample on vegetables before treatment was given. There is an increase in students’ knowledge of vegetables after being given treatment with lectures and media of vegetable cards. Conclusion: Couseling about vegetables using vegetable card media was more effective than treatment with lecture method toward improvement of elementary school student knowledge. Keywords: Counseling, vegetables, cards, elementary school student